Intracranial Meningioma in a Dog - Treatment with Radiotherapy - Araujo, Dayane Caicó Collares; Cunha, Simone Carvalho dos Santos; Schamall, Ragnar Franco; Fernandes, Julio Israel (Acta Scientiae Veterinariae, 2022)
Background: The most common primary brain neoplasm is meningioma. Dolichocephalic breeds are predisposed and there is no sexual predilection. Clinical signs depend on the location and size of the tumor and have a progressive course. Primary treatement includes surgery, radiotherapy or both. This study aimed to describe the treatment of a dog with suspected intracranial meningioma with definitive radiotherapy, which resulted in significant clinical improvement and prolonged survival. Case: A 9-year-old Shetland Shepherd bitch was diagnosed with a head tilt to the left side that progressed over a few weeks. She previously received corticosteroid therapy, which resulted a clinical improvement that worsened after treatment was discontinued. Computed tomography revealed an extra-axial brain mass in the caudal fossa, lateralized to the right, well-delimited, and measuring approximately 1.5 × 1.4 × 1.7 cm, suggestive of intracranial meningioma. The patient was treated with radiotherapy using Cobalt-60 equipment, with 18 daily fractions of 2.5 Gy at a total dose of 45 Gy using parallel and opposite technique fields. A new tomography performed 30 days after treatment showed a remission of 85% of the initial brain mass measuring approximately 0.9 × 1.0 × 0.5 cm, as well as complete resolution of the clinical signs initially presented. After 14 months, the patient presented with signs of lethargy and ataxia and was medicated with hydroxyurea at a dose of 50 mg/kg 3 times a week and corticosteroid therapy. However, the patient’s neurological condition deteriorated, and she was subjected to reirradiation using the same protocol used previously, which resulted in clinical improvement and a 54% reduction in tumor volume on magnetic resonance. As a late side effect, only permanent alopecia in the irradiated region was observed. The patient died of disease 330 days after the second course of radiotherapy, with a total survival time of 1087 days. Discussion: Meningiomas are extra-axial neoplasms of the central nervous system that grow inside the dura mater. The literature shows that meningiomas are more common in dolichocephalic races with a mean age of 9 years, which supports our findings. Meningiomas most commonly affect the cortical thalamus and cerebellopontine region in dogs, which are normally associated with vestibular symptoms, as seen in this case. Diencephalic damage can result in vestibular signals since the thalamus functions as a relay station for vestibular afferent stimuli that are relayed to the cerebral cortex. In addition to the vestibular syndrome, common clinical signs associated with meningiomas in dogs include seizures, behavioral changes, and walking in circles, which are frequently misinterpreted due to tumor-induced side effects, such as cerebral edema, obstructive hydrocephalus, and cerebral hernia. Advanced imaging techniques should be used to diagnose intracranial neoplasms. In this case, computed tomography was critical for diagnosis and treatment planning. Meningioma treatment may comprise palliative measures, surgery, and radiotherapy. Radiotherapy as a single treatment can improve the quality of life with a decrease in clinical signs and a median survival time of approximately 250-536 days, as reported in the literature. Hydroxyurea can be a therapeutic option in inoperable cases and for patients with clinical limitations to undergo successive anesthesia during radiotherapy. Its most serious side effect is progressive myelosuppression. It can cause temporary partial tumor remission and improvement in clinical signs. As previously stated, radiotherapy can be an effective primary treatment option for treating intracranial meningiomas in dogs, with significant improvement in neurological clinical signs and mild side effects. Keywords: dogs, central nervous system, radiotherapy, reirradiation, oncology. Título: Meningioma intracraniano em cão - tratamento com radioterapia Descritores: cães, sistema nervoso central, radioterapia, reirradiação, oncologia.